Development of a Microscopic Colitis Disease Activity Index: a prospective cohort study. Issue 3 (13th December 2016) - Cotter, Thomas G; Binder, Moritz; Loftus, Edward V; Abboud, Rami; McNally, Meredythe A; Smyrk, Thomas C; Tremaine, William J; Sandborn, William J; Pardi, Darrell S
Abstract : Objective: Microscopic colitis (MC) is a common cause of chronic diarrhoea, often with additional symptoms. No validated instruments exist to assess disease activity in MC, making it difficult to compare efficacy of treatments between clinical trials. We aimed to identify clinical features that independently predicted disease severity and create a Microscopic Colitis Disease Activity Index (MCDAI). Design: Patients with MC were prospectively administered a survey assessing their GI symptoms and the IBD Questionnaire (IBDQ). A single investigator also scored a physician global assessment (PGA) of disease severity on a 10-point scale. Multiple linear regression identified which symptoms best predicted the PGA. These symptoms were then combined in a weighted formula to create the MCDAI. The relationship between MCDAI and the IBDQ was investigated. Results: Of the 175 patients enrolled, 13 (7.4%) did not complete the survey. The remaining 162 had a median age of 66 years (range, 57–73) and 74% were female. Several clinical features were independently associated with PGA (number of unformed stools daily, presence of nocturnal stools, abdominal pain, weight loss, faecal urgency and faecal incontinence). These parameters were combined to create the MCDAI, which strongly predicted the PGA (R 2 =0.80). A 1-unit decrease in disease activity (ΔMCDAI) was associated with a 9-unit increase in quality of life (ΔIBDQ). Conclusions: The MCDAI strongly predicted the PGA and correlated with a validated measure of quality of life. Several symptoms in addition to diarrhoea are associated with disease severity in MC.